Pengembangan Model Aksi Antisipatif Berbasis Kolaborasi Multi-Pihak dalam Kesiapsiagaan Banjir Kabupaten Pandeglang - Pakpahan, Roy Tumpal (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze and develop an anticipatory action model based on multi-stakeholder collaboration for flood preparedness in Pandeglang Regency, where flood management practices have predominantly relied on reactive emergency response measures. The primary issue identified is the limited institutionalization of anticipatory actions during the pre-disaster phase, weak cross-sector coordination, insufficient resource integration, and minimal engagement of community groups and non-governmental stakeholders in preparedness planning. The research employs a descriptive qualitative approach, collecting data through in-depth interviews, field observations, and analysis of regional policy and contingency planning documents. Data were analyzed using an interactive process consisting of data collection, reduction, display, and conclusion drawing to identify patterns of collaboration, governance gaps, and structural constraints. The findings reveal that although formal contingency planning documents exist, anticipatory measures have not been systematically implemented or embedded within routine governance practices. This study proposes a conceptual model that emphasizes institutionalized collaboration, clearly defined stakeholder roles, strengthened early warning systems, integrated pre-disaster planning mechanisms, sustainable resource allocation, and active community participation. The proposed model contributes to the development of proactive, inclusive, and sustainable flood governance while enhancing local resilience and reducing long-term disaster risk in flood-prone regions.